THE INFLUENCE OF QUALITY, PRICE, LOCATION, PROMOTION AND COMPANY IMAGE ON HOUSE PURCHASE DECISIONS AT PT. FIRYA RESIDENCE LIENTS IN THE CITY LHOKSEUMAWE - Syerina Dwi; Sapna Biby; Agustinawati; M.Subhan (RADJA PUBLIKA, 2024)
This research aims to see the influence of quality, price, location, promotion, and company image on house purchasing decisions at PT. firya lientas residence in Lhokseumawe city. The type of data used is primary data. The research sample consisted of 66 respondents. The data analysis method used to see the relationship between the independent variable and the dependent variable uses multiple linear regression. The results of this research indicate that partial product quality has a positive and significant effect on house purchasing decisions at PT. Firya Lientas Residence Kota Lhokseumawe, the price has a negative and significant effect on house purchasing decisions at PT. Firya Lientas Residence Lhokseumawe City, location has a positive and significant effect on house purchasing decisions at PT. Firya Lientas Residence Kota Lhokseumawe, the promotion has a positive and significant effect on house purchasing decisions at PT. Firya Lientas Lhokseumawe City residence and company image have a positive and significant influence on house purchasing decisions at PT. firya lientas residence city of lhokseumawe.